Konsep Hermeneutika Menurut Muhammed Arkhoun - Oktaviana, Anisa Rosi (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2021)
At the beginning of the emergence of hermeneutic studies, its characters used this approach to interpret the Bible. Then the more this science began to develop, finally a thought emerged that the exegetical methods applied to the Bible could also be applied to other books. In other words, other holy books can also be interpreted using the hermeneutic approach. In the postmodernism era, Muslim figures and their thoughts emerged. One of them is Mohammed Arkoun, because he has lived in France for a long time and has been appointed as a lecturer at Sorbonne University, many of his thoughts are oriented to figures, especially western linguistic figures. He tried to interpret the Qur'an using the Hermeneutic method. The research method used is descriptive qualitative research, where the data source is in the form of documents related to this research. The result is Arkoun's phenomenal thinking about the interpretation of